Longitudinal Variations of CDC42 in Patients With Acute Ischemic Stroke During 3-Year Period: Correlation With CD4+ T Cells, Disease Severity, and Prognosis - Cheng, Xiao; Ye, Jianxin; Zhang, Xiaolei; Meng, Kun (Frontiers in Neurology, 2022)
Objective Cell division cycle 42 (CDC42) modulates CD4+ T-cell differentiation, blood lipids, and neuronal apoptosis and is involved in the pathogenesis of acute ischemic stroke (AIS); however, the clinical role of CDC42 in AIS remains unanswered. This study aimed to evaluate the expression of CDC42 in a 3-year follow-up and its correlation with disease severity, T helper (Th)1/2/17 cells, and the prognosis in patients with AIS. Methods Blood CDC42 was detected in 143 patients with AIS at multiple time points during the 3-year follow-up period and in 70 controls at admission by reverse transcription-quantitative polymerase chain reaction (RT-qPCR). In addition, blood Th1, Th2, and Th17 cells and their secreted cytokines (interferon-γ (IFN-γ), interleukin-4 (IL-4), and interleukin-17A (IL-17A)) in patients with AIS were detected by flow cytometry and enzyme-linked immunosorbent assay (ELISA), respectively. Results Compared with controls (p < 0.001), CDC42 was reduced in patients with AIS. CDC42 was negatively correlated with the National Institutes of Health Stroke Scale (NIHSS) score (p < 0.001), whereas, in patients with AIS (all p < 0.050), it was positively associated with Th2 cells and IL-4 but negatively correlated with Th17 cells and IL-17A. CDC42 was decreased from admission to 3 days and gradually increased from 3 days to 3 years in patients with AIS (P<0.001). In a 3-year follow-up, 24 patients with AIS recurred and 8 patients died. On the 3rd day, 7th day, 1st month, 3rd month, 6th month, 1st year, 2nd year, and 3rd year, CDC42 was decreased in recurrent patients than that in non-recurrent patients (all p < 0.050). CDC42 at 7 days (p = 0.033) and 3 months (p = 0.023) was declined in reported deceased patients than in survived patients. Conclusion CDC42 is used as a biomarker to constantly monitor disease progression and recurrence risk of patients with AIS.